2000
DOI: 10.1023/a:1008155230143
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: We study by molecular dynamics simulations the hydration of beta-cyclodextrin. Our simulations show that within these barrel-shaped molecules hydrophobicity dominates, while at the top and bottom sides of the barrel interactions with water are mostly hydrophilic in nature. These results agree with crystallographic data at 120 K and, in particular, with the spontaneous hydration process of a cyclodextrin crystal in wet atmosphere. The predicted structure of the hydration shells is discussed and compared with pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
29
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 6 publications
3
29
0
Order By: Relevance
“…The hygroscopic property of b-CD is because the outside of the b-CD torus shape is typically hydrophilic and water molecules are easily adsorbed, and the cavity also contains weak hydrophilic and water binding sites (Martin Del Valle, 2004;Tanada, Nakamura, Kawasaki, Kurihara, & Umemoto, 1996). From crystallographic study (Lindner & Saenger, 1982) and molecular dynamics simulation study (Winkler, Fioravanti, Ciccotti, Margheritis, & Villa, 2000), it was reported that b-CD is associate with 12 water molecules to form a dodecahydrate. Our result of 12.36 mol of water absorbed by b-CD is in agreement with the reports.…”
Section: Resultsmentioning
confidence: 99%
“…The hygroscopic property of b-CD is because the outside of the b-CD torus shape is typically hydrophilic and water molecules are easily adsorbed, and the cavity also contains weak hydrophilic and water binding sites (Martin Del Valle, 2004;Tanada, Nakamura, Kawasaki, Kurihara, & Umemoto, 1996). From crystallographic study (Lindner & Saenger, 1982) and molecular dynamics simulation study (Winkler, Fioravanti, Ciccotti, Margheritis, & Villa, 2000), it was reported that b-CD is associate with 12 water molecules to form a dodecahydrate. Our result of 12.36 mol of water absorbed by b-CD is in agreement with the reports.…”
Section: Resultsmentioning
confidence: 99%
“…The cavity of "empty" βCD can admit -five to six water molecules [12]; therefore, the value I 3 /I 1 = 1.55 corresponds to the vibronic structure of the fluores cence spectrum of pyrene involved in the aggregate (H 2 O) n ⋅ (Py@4βCD), where n = 10-12, and, starting from this value, I 3 /I 1 further increases after the addi tion of other analytes. We obtained values of I 3 /I 1 for analytes of different polarity (benzene, toluene, hex ane, cyclohexane, and methylcyclohexane) and polar liquids (ethanol, acetone, and acetonitrile).…”
Section: Change In the Vibronic Structure Of Pyrene Fluorescence Specmentioning
confidence: 99%
“…Molecular dynamics (MD) simulations are more timeconsuming but provide a better connection between atomistic constitution and macroscopic properties when compared to pure geometry optimizations methods. 29 In addition to structural [30][31][32]35,36,39,41 and solvation 33,34,[37][38][39][40][41][42][43] aspects, dynamic information can be monitored. The latter is essential to the understanding of the properties and mechanisms involved in host-guest complexation.…”
mentioning
confidence: 99%